ANALISIS ISI OPINI KOMPASIANER TERHADAP IMPLEMENTASI UNDANG – UNDANG NOMOR 19 TAHUN 2016 TENTANG INFORMASI, TRANSAKSI, DAN ELEKTRONIK - Aqsa Rahardian; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
Legislation – Act No. 19 of the year 2016 about information, electronic and transactions,  is the first cyber law regulations in Indonesia that applies since 2016. As the first new legal regulation, the implementation of UU ITE full pros – cons in its implementation. In an era of technological development, kompasiana.com is present as the online media (citizen journalism) where anyone can convey opinions. The purpose of this research was to know how big the rate trend of opinion from a user called kompasiana.com with kompasianer against the implementation of UU ITE No. 19 year 2016. The theory used in this study is the S-R theory. Since enforced the ACT ITE 2016 years no. 16 gave a stimulus to the community against the implementation of the ACT ITE with response in the form of opinion pro or con. This research using quantitative content analysis of research methods, data collection techniques, namely through the documentation of kompasianer opinion in the kompasiana.com. The samples on this research totalled 16 opinion by using the method of Total Sampling. Methods of data analysis used is a frequency distribution table. The data processing is done by either using a coding sheet. The results obtained from this study is conduded that 50% of kompasianer’s opinion on the implementation of the ITE LAW No.19 of the year 2016 tends to be neutral. This is evidenced the content of opinion contains that some of criticism, praise, and advice. The implementation of the ITE LAW No. 19 of 2016 is still felt less precise so that the existing opinion contains elements of criticism. Nevertheless, there are opinions that praise the implementation of the ITE LAW No. 19 of 2016 and also there are some advise that the implementation of the ITE LAW No. 19 of 2016 to be more effective. Keywords : Opinion, Stimulus Respon, Content Analysis, New Media